Master Fryer Enterprise : Burger Patty Fryer / Abdul Hakim Azmi ...[et al.] - Azmi, Abdul Hakim; Rafie, Aizat; Hashim, Adam Harith; Junaidi, Abd Rahman; Md Halil, Amirul Syafiq; Omar, Muhammad Giri (2016)
Master Fryer is a company that focuses our skills and knowledge on burger patty frying in Malaysia. Burger making is a very annoying and time-consuming task. Usually, burger is fried on regular gas stove. Our company would like to solve this problem to ease the life of the people. Thus, we have created and developed a very reliable and innovative product specifically to fry burger patty. From the concept of sandwich toaster, we have made a very special innovation and the burger patty fryer is created. Our product uses electricity and heating element instead of regular gas stove just like a sandwich toaster. It has a lid and the burger patty will fry all the way without troubling the user to flip the burger patty.